A review of the Margarodidae sensu stricto (Hemiptera: Coccomorpha) in China, with descriptions of three new species - Zheng, Xinyi; Wu, San’an (Zootaxa, 2024)
The research history of the family Margarodidae Cockerell sensu stricto (Hemiptera: Coccomorpha) from China is reviewed. Four species of Porphyrophora Brandt and three species of Neomargarodes Green from China are described and illustrated, including three new species: Neomargarodes chenopodium Zheng & Wu, sp. nov. based on the morphology of the adult female, first-instar nymph and second-instar female and male nymphs (cysts); Porphyrophora ejinensis Zheng & Wu, sp. nov. based on the adult female, second-instar female nymph (cyst) and third-instar female nymph (cyst); and Porphyrophora neimonggolensis Zheng & Wu, sp. nov. based on the adult female. Porphyrophora ningxiana Yang, 1979, stat. rest. is resurrected from synonymy under Porphyrophora sophorae (Archangelskaya, 1935), and lectotypes of Neomargarodes gossypii Yang, 1979 and P. ningxiana Yang are designated. A record of Porphyrophora ussuriensis Borchsenius, 1949 from China was found to be based on a misidentification. An identification key to genera and species of Margarodidae s.s. found in China is provided, based on adult female morphology.